Assessment of anti-bacterial activity and brine shrimp toxicity of two Polygonum species - MAZID, MA; DATTA, BK; NAHAR, L; SARKER, SD (Ars Pharmaceutica (Internet), 2008)
The extracts of the aerial parts of Polygonum barbatum var. barbata and Polygonum stagninum (Family: Polygonaceae)were assessed for anti-bacterial activity against a number of bacterial strains using the disc diffusion assay, andbrine shrimp toxicity using the brine shrimp lethality assay. All extracts/fractions, except the MeOH extract/fraction,exhibited low to moderate levels of anti-bacterial activity against most of the test strains (zone of inhibition = 7-21mm). All extracts and fractions displayed considerable general toxicity towards brine shrimps. The LD50 values of thetest extracts/fractions were within the range of 2.19 to 114.81 mg/mL, whereas that of the positive control (vincristinesulphate) was 0.61 mg/mL.